2020
DOI: 10.3390/en13092127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Energy Utilization Index in Sheep Milk Cooling Systems

Abstract: The energy consumption of sheep milk cooling systems (MCSs) was quantified in this study to provide original information filling a literature gap on the impact of sheep milk cooling on the energy and economic balance in dairy farms. Performance and energy monitoring tests were conducted simultaneously on 22 MCSs in Sardinia (Italy). The results determined the cooling time as a function of the performance class and number of milkings. The Energy Utilization Index (EUI) was applied to measure the energy required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Kanyarushok et al ( 2008) conducted a study on goat milk in France, finding that per FPCM, a total of 5.06 MJ was required, of which 3.87 was allocated to feed and 1.19 to on-farm production [59], while Idele (2011) found that 4.9 MJ was required per FPCM of sheep milk (no breakdown provided). This is supported by Cossu et al's (2020) study on milk cooling, which found that the energy input for sheep milk cooling was significantly higher than cow's milk [60].…”
Section: Sheep and Goatmentioning
confidence: 64%
“…Kanyarushok et al ( 2008) conducted a study on goat milk in France, finding that per FPCM, a total of 5.06 MJ was required, of which 3.87 was allocated to feed and 1.19 to on-farm production [59], while Idele (2011) found that 4.9 MJ was required per FPCM of sheep milk (no breakdown provided). This is supported by Cossu et al's (2020) study on milk cooling, which found that the energy input for sheep milk cooling was significantly higher than cow's milk [60].…”
Section: Sheep and Goatmentioning
confidence: 64%